2020
DOI: 10.1016/j.ijrobp.2019.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Thermal Imaging Biomarkers to Detect Acute Skin Toxicity From Breast Radiation Therapy Using Supervised Machine Learning

Abstract: Radiation-induced dermatitis is a common side effect of breast radiotherapy (RT).Current methods to evaluate breast skin toxicity include clinical examination, visual inspection, and patient-reported symptoms. Physiological changes associated with radiation-induced dermatitis, such as inflammation, may also increase body-surface temperature which can be detected by thermal imaging. Quantitative thermal imaging markers were identified using supervised machine-learning to develop a predictive model for radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…CTCAE scales were found to be associated with a * and L * values, which are indicators of skin color alteration [ 13 ]. Saednia et al [ 17 ] reported that thermal imaging markers could be used to monitor RIT. Patients with a CTCAE toxicity score > 2 demonstrated a significant increase in skin temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTCAE scales were found to be associated with a * and L * values, which are indicators of skin color alteration [ 13 ]. Saednia et al [ 17 ] reported that thermal imaging markers could be used to monitor RIT. Patients with a CTCAE toxicity score > 2 demonstrated a significant increase in skin temperature.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid this bias, many objective assessment tools have been introduced for monitoring skin changes more accurately, including ultrasound [11][12][13], reflectance spectrophotometry [14][15][16], thermal images [17], laser Doppler flowmetry (LDF) [18] and other multiprobe devices which consists of various probes that can assess different skin parameters, including erythema, pigmentation, hydration; skin pH, skin temperature etc. [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Few implementations of ML non-related to breast cancer diagnosis were found. Zadeh et al used fuzzy active contours to segment suspected breast tumor areas (ACC = 91.89%) and Saednia et al developed a supervised ML algorithm based on Random Forest to assess dermatitis caused by radiation therapy, reporting thermal markers indicative of radiation-induced skin toxicity with an ACC of 87% [51].…”
Section: Breast Cancermentioning
confidence: 99%
“…Current available literature includes only one abstract (11) and two full papers (10,12). In the study by Saednia et al, they proposed an innovative approach based on the detection of bodysurface temperature increase induced by radiation dermatitis.…”
Section: Breastmentioning
confidence: 99%
“…The Supplementary Material for this article can be found online at: https://www.frontiersin.org/articles/ 10…”
Section: Supplementary Materialsmentioning
confidence: 99%